Chapter "Vinci te stesso e vincerai il mondo". Le fonti di un aforisma rinvenibile nelle opere di Dostoevskij dell'ultimo periodo - Cavazza, antonella (Biblioteca di Studi Slavistici, 2019)
Notable among the stylistic tools adopted by Dostoevskij to disseminate the values that he considered crucial for the moral revival of contemporary Russian society is the use of the aphorism. This article explores the origins of the renowned maxim "If you want to overcome the whole world, overcome yourself", a phrase that recurs either in this form or with some variation in the literary and journalistic texts that Dostoyevsky authored towards the end of his life. His sources include Saint Augustine, Thomas à Kempis, and Prosper of Aquitaine.